EGFR T790M ctDNA testing platforms and their role as companion diagnostics: Correlation with clinical outcomes to EGFR-TKIs. (10th September 2017) - Liang, Zhiyong; Cheng, Ying; Chen, Yuan; Hu, Yanping; Liu, Wei-Ping; Lu, You; Wang, Jie; Wang, Ye; Wu, Gang; Ying, Jian-Ming; Zhang, He-Long; Zhang, Xu-Chao; et al.
Abstract: Somatic mutation in the epidermal growth factor receptor (EGFR) predict clinical response to EGFR tyrosine kinase inhibitors in non-small cell lung cancer (NSCLC) and is a promising target for personalised medicine. EGFR mutations have prognostic value. Initially patients respond well to tyrosine kinase inhibitors but finally they would develop resistance and about 50% of this resistance can be attributed to the emergence of EGFR resistant mutation, T790M. This necessitates the need for genetic testing for clinical management of patients. Molecular testing has become the standard of care in patients with NSCLCs based on the recommendations of standard guidelines. Though there are several platforms for EGFR mutation detection, highly sensitive platforms for clinical applicability as companion diagnostics for ctDNA based testing are emerging. Due to the dynamic changes in the T790M mutation during tyrosine kinase inhibitor (TKI) treatment, real-time monitoring of these genetic alterations is mandate for planning treatment strategies. With the advent of third generation TKIs that potentially target T790M, improvement in clinical outcome is documented in patients with NSCLCs. Managing these outcomes with appropriate companion diagnostics using ctDNA in early detection of these genetic alterations will improve patient care. Highlights: Treatment strategies in NSCLC are driven by somatic mutations in EGFR gene. About 50% of patients with NSCLC on tyrosine kinase inhibitor acquire resistance due to emergence of T790M mutation. Real time monitoring of T790M mutation is necessary for assessing clinical outcomes of TKIs. ctDNA is a feasible and less-invasive method for monitoring and managing advanced drug resistant NSCLC patients.